2021
DOI: 10.1108/jfmpc-03-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the risk factors in real estate construction projects: an analytical study to propose a control structure for decision-making

Abstract: Purpose Construction projects in the real estate sector are important for a nation’s economic growth. However, owing to several constraints and stereotypes, the construction industry is suffering from major capital losses. A review of recent literature revealed that risks occurring in real estate construction projects (RECPs) carried out in developing economies can be divided into four categories, i.e. financial risks, design risks, execution risks and sociopolitical risks. This study aims to identify the crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 74 publications
(154 reference statements)
0
19
0
1
Order By: Relevance
“…For the supply side, the real estate sector is inherently capital-intensive, and developers typically rely on indirect financing from banks (Deep et al, 2022). An increase in lending rates directly impacts the financing costs for developers, dampening their willingness to invest.…”
Section: Monetary Policy and Its Transmission Mechanismmentioning
confidence: 99%
“…For the supply side, the real estate sector is inherently capital-intensive, and developers typically rely on indirect financing from banks (Deep et al, 2022). An increase in lending rates directly impacts the financing costs for developers, dampening their willingness to invest.…”
Section: Monetary Policy and Its Transmission Mechanismmentioning
confidence: 99%
“…Servicing for damaged equipment (sfl = 0.813) and knowledge of the equipment (sfl = 0.697) are another other factor, as the owner of the equipment does not maintain proper maintenance records and spends less on its maintenance [29]. The forcing of major delays, e.g., the impact of weather conditions on a project (sfl= 0.686) was also grouped under this category, as the occurrence of force of nature events is difficult to predict, but it can heavily constrain the project [47,48]. Lastly, the chances of the subcontractors walking out of the project (sfl = 0.676) can have a critical impact on the performance and delivery of highway projects.…”
Section: Execution Constraintsmentioning
confidence: 99%
“…The first variable, i.e., a delay in work execution of a sub-contractor (sfl = 0.985), cannot be planned and is only resolved by switching the subcontractor [47,[49][50][51][52]. It has been commonly observed that in all types of construction projects, opportunism has been a dominant phenomenon, and under its influence the parties involved in construction activities are concerned about their profit margins [48,53]. As a result, they tend to delay work execution by making frequent claims; thus, under such a situation, the project organization situation the project organisation should demonstrate a robust communication, claim-settlement, and conflict avoidance mechanism [49].…”
Section: Operational Factorsmentioning
confidence: 99%
“…Construction is a highly risk-prone industry [45], and the risks of PBPs are more prominent than those of traditional buildings [30]. No project is risk-free [46], but effective risk management can minimize the impact of risk [47]. Therefore, many researchers believe that it is necessary to take risk management as an important part of project management in PBPs [48].…”
Section: Risk Management Of Pbpsmentioning
confidence: 99%
“…Luo et al [20] explored the supply chain risks of the identified 30 PBPs in Hong Kong using social network analysis (SNA), and finally came up with three main challenges and gave specific response strategies. Identifying the risks in PBPs accurately and proposing strategies for different types of risks is a common research process in the current risk management of PBPs [46,47].…”
Section: Risk Management Of Pbpsmentioning
confidence: 99%